1986
DOI: 10.1088/0268-1242/1/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of InGaAs-InP quantum wells by optical spectroscopy

Abstract: A detailed study of the optical properties of InGaAs-lnP single quantum wells (aws) grown by atmospheric-pressure metal-organic chemical vapour deposition is described. Photoluminescence (PL), photoluminescence excitation (PLE), photoconductivity (PC) and electroreflectance (ER) are employed to study both undoped and modulation-doped quantum wells. The role of extrinsic processes in determining the low-temperature PL spectra is demonstrated from the variation of peak position and linewidth with temperature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
52
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(64 citation statements)
references
References 30 publications
12
52
0
Order By: Relevance
“…16 -20 Several studies have shown that in QW heterostructures, random fluctuations of the alloy composition and roughness of the barrier-well interfaces are determinant factors of sample quality. [21][22][23][24] These defects create fluctuations in the confinement potential and lead to the formation of a band tail in the excitonic density of states. 18,[23][24][25] Depending on the energy excess ͑obtained from the laser pumping energy͒ and the magnitude of the potential fluctuation, the excitons will relax either to the local minima or to the absolute minimum of the confinement potential via phonon emission before the radiative recombination takes place.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 -20 Several studies have shown that in QW heterostructures, random fluctuations of the alloy composition and roughness of the barrier-well interfaces are determinant factors of sample quality. [21][22][23][24] These defects create fluctuations in the confinement potential and lead to the formation of a band tail in the excitonic density of states. 18,[23][24][25] Depending on the energy excess ͑obtained from the laser pumping energy͒ and the magnitude of the potential fluctuation, the excitons will relax either to the local minima or to the absolute minimum of the confinement potential via phonon emission before the radiative recombination takes place.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23][24] These defects create fluctuations in the confinement potential and lead to the formation of a band tail in the excitonic density of states. 18,[23][24][25] Depending on the energy excess ͑obtained from the laser pumping energy͒ and the magnitude of the potential fluctuation, the excitons will relax either to the local minima or to the absolute minimum of the confinement potential via phonon emission before the radiative recombination takes place. 17,19 Therefore, the PL spectrum reflects the exciton distribution in the energy states generated by potential fluctuations.…”
Section: Methodsmentioning
confidence: 99%
“…This increase of localized states with increasing content of alloyed atoms and dopants leads to an increase of Stokes' shift and broadening of the emission and absorption edges. 7,[9][10][11][12][13] These effects are observed in various structures such as quantum well structures, [14][15][16][17][18][19][20] quantum dot structures in alloyed semiconductors, 7,9,10 and heavily doped semiconductors. 12,13 In view of the structure and experimental results, the results in this investigation are closer to quantum dot model in alloyed semiconductors.…”
Section: ͑Ev͒ ͑1͒mentioning
confidence: 99%
“…14 -16 The following qualitative explanation of the anomalous temperature behavior of the emission band in semiconductors was proposed to interpret the observation of this phenomenon in InGaAs/InP single quantum wells. 17 An initial temperature-induced redshift of the band peak was attributed to an increased mobility of excitons and, hence, their ability to move over longer distances to deeper localized states. The blueshift that is observed with further increase of the temperature was attributed to the population of the localized exciton states with increasingly higher energy, whereas the subsequent redshift is due to the typical band gap shrinkage with temperature.…”
mentioning
confidence: 99%